A patient with oeosinophilic gastroenteritis and severe malnutrition improved with home parenteral nutrition. (12th November 2010) - Santarpia, Lidia; Cuomo, Rosario; Camera, Luigi; Alfonsi, Lucia; Contaldo, Franco; Pasanisi, Fabrizio
Abstract : Oeosinophilic gastroenteritis is a chronic and rare disorder characterised by massive oeosinophilic tissue infiltration involving one or more segments of the digestive tract. The management of patients with oeosinophilic gastroenteritis is complex and the therapeutic response often poor. Here we discuss the clinical case and management of a 23-year-old man with oeosinophilic gastroenteritis since the first year of life and the decision to prescribe lifelong total parenteral nutrition.